Situation Report: Baltic Area, 29 August 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The New Five-Year Plan / by Uku Kuusk Youth Trends: Breakdancing in, Heavy Metal in Trouble / by Toomas Ilves Ecologic Concern in Estonia / by Uku Kuusk Party Secretary Promoted to USSR Minister / by Toomas Ilves Party Second Secretary Named Soviet Ambassador / by Uku Kuusk The 800th Anniversary of Christianity in Latvia / by Dzintra Bungs Dissident Paroled / by Dzintra Bungs Privately Run Cafes in Riga / by Dzintra Bungs The 70th Issue of the Lithuanian Catholic Chronicle / by Jonas Papartis Automobile Repairs in Lithuania / by Saulius Girnius